The Roles of Community Engagement and Brand Community Types in Building Brand Trust on Social Media Based Brand Communities - Kurniadi Prastowo (International Journal of Business Studies, 2020)
This study aims to understand the influence of the four elements of the relationship or customer- centric model in the online brand community (relationship between customer-product, customer-brand, customer-company, and customer-other customers) on brand trust in the realm of social media, by measuring moderation effects of community engagement and brand community types. The respondents are 220 respondents, coming from two types of brand community: consumer-initiated and company-initiated brand community. In general, the measurement is done by using structural equation modeling method. The results obtained from the analysis of this study are from the four elements of existing relationships in the online brand community (customer relationships with product, brand, company, and other customers), only customer-brand relationships that significantly affects brand trust. The results are different from previous studies, so it is interesting to investigate further. Furthermore, this research also found moderation effect of community engagement and community types in the relationship between online brand community and brand trust.